Audio Arts : Beunruhigende Versuche zur Genauigkeit. - Furlong, William; Archer, Michael; Beuys, Joseph; Frawley, Miranda; Furlong, William; Gooding, Mel; Hamilton, Richard; Kabakov, Ilya; Kapoor, Anish; Lichtenstein, Roy; Livingstone, Marco; Lloyd, Jill; et al. (Leipzig : Reclam-Verlag, 1992)
Abramovic, Marina ; Acconci, Vito ; Adam, Judy ; Adams, Yura ; Akinson, Terry ; Amikhaniran, Charles ; Anastasi, William ; Anderson, Laurie ; Anderson, Ruth ; Andre, Carl ; Apple, Jacki ; Archer, Michael ; Arensberg ; Arp, Hans (Jean) ; Atkinson, Conrad ; Barker, Barry ; Baroni, Vittore ; Barthes, Roland ; Beckley, Connie ; Van Beethoven, Ludwig ; Beuys, Joseph ; Beyer, Johanna ; Birnbaum, Dara ; Blacker, Kate ; Böhmler, Claus ; Boone, Mary ; Branca, Glenn ; Breakwell, Ian ; Brenson, Michael ; Breshnew, Leonid ; Brisley, Stuart ; Brown, Earl ; Brush, Leif ; Brusky, Paulo ; Bryars, Gavin ; Buckminster Fuller, Richard ; Buddha ; Burden, Chris ; Burroughs, William ; Cage, John ; Cardew, Cornelius ; Carson, John ; Castelli, Leo ; Cézanne, Paul ; Chadwick, Helen ; Childs, Lucinda ; Chomsky, Noam ; Clemente, Francesco ; Corot, Jean-Baptiste Camille ; Courbet, Gustave ; Crevel, René ; Cunningham, David ; Cunningham, Merce ; David, Jacques-Louis ; Deconingrad ; Degas, Edgar ; Dimitrijevic, Braco ; Dix, Otto ; Doherty, Brian ; Donaghee, Catherine ; Duchamp, Marcel ; Eisenstein, Sergej ; Ess, Barbara ; Evans, Christopher ; Feldman, Morton ; Feldmann, Robert ; Fishbein, Sue ; Fitzgerald, Zelda ; Foreman, Richard ; Forrell ; Fox, Terry ; Francis, Mark ; Frangione, Nicola ; Frawley, Miranda ; Freud, Lucian ; Friedrich, Caspar David ; Furlong, William ; Garland, David ; Garrard, Rose ; George, Bob ; Glass, Philip ; Goethe, Wolfgang von ; van Gogh, Vincent ; Goldstein, Jack ; Gooding, Mel ; Gordon, Jeff ; Gordon, Peter ; Graves, Maurice ; Greenberg, Clement ; Groh, Klaus ; Hahn, Christine ; Haimsohn, Jana ; Hall, Adrian ; Hamilton, George Heard ; Hamilton, Richard ; Harrison, Margaret ; Hathaway, Henry ; Haymon, Mark ; Heidsieck, Bernhard ; Heyward, Julia ; Hiller, Susan ; etc.
Duits & Engels
boek